Demographic and clinical features of nontuberculous mycobacteria infection resulting from cosmetic procedures: a systematic review - Xiao Ma; Xing-Yu Li; Jia-Wei Liu (International Journal of Infectious Diseases)
Objectives: This systematic review aims to (1) summarize the demographic and clinical characteristics of patients with nontuberculous mycobacterial (NTM) infections following cosmetic procedures; (2) summarize the frequency of pathogenic NTM species; and (3) review and analyze the antibiotics choice as well as treatment outcomes. Methods: We conducted a systematic search of three electronic databases (Scopus, Embase, and PubMed) from inception to March 31, 2024. We presented demographic and clinical features and the main antibiotic strategy, along with etiological information. Results: A total of 200 patients were included in the analysis, with a median onset age of 38.0 years. The median latency period before the illness was 28 days. Nodules were the most frequently reported type of lesion, occurring in 31.0% (n = 62/200) of cases. Mycobacterium abscessus was the most commonly found NTM (45%). Clarithromycin was the most commonly applied (64.0%, n = 128/200), followed by amikacin (31.0%, n = 62/200). The median treatment duration was 6 months (0.25, 24). The overall treatment effectiveness rate was 97.4% (n = 148/152). Conclusion: NTM infections caused by cosmetic procedures are rapidly increasing worldwide and present diagnostic and treatment challenges. Dermatologists and aesthetic practitioners should be aware of this relatively uncommon disease. Further research is needed to standardize management algorithms.